IAES International Conference on Electrical Engineering, Computer Science and Informatics - Munawar A Riyadi; Sri Arttini Dwi Prasetyowati; Tole Sutikno; Deris Stiawan (IAES Indonesia Section, 2016)
The 3rd International Conference of Electrical Engineering, Computer Science and Informatics (EECSI) 2016 was held in Semarang, Indonesia from 23th to 25thNovember, 2016. The conference was organized by Universitas Islam Sultan Agung as the host in collaboration with Universitas Diponegoro, Universitas Ahmad Dahlan and Universitas Sriwijaya, and with full technical support from IAES Indonesia Section. Authors and participants from 10 countries made the conference truly international in scope. Participants have delivered their talks of valuable research outputs that vary from many fields of electrical engineering (power electronics, telecommunication, electronics engineering, control system and signal processing) to the field of computer science and informatics. These wide range of topics have colorized this conference.This volume of IOP Conference Series: Materials Science and Engineering contains selected articles from those presented in the conference. After presentation, the revised papers were peer reviewed by fellow reviewers to ensure the quality of published materials. Finally, Editors decided to select and publish as many as 49 papers. It is hoped that the presented papers can offer more insight towards broad audience.On behalf of Editors, we appreciate enormous work of all staffs and reviewers in the preparation of this volume. We would like to express our sincere thanks to all authors and presenters for their valuable contributions. We hope to see you again in the next event of EECSI 2017 which will be held in Yogyakarta, Indonesia, next year.